IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NHT UNTUK MENINGKATKAN HASIL BELAJAR PJOK PADA PESERTA DIDIK KELAS XI A2 SMA NEGERI 2 DENPASAR TAHUN PELAJARAN 2025/2026 - I Gusti Ngurah Panca; I Wayan Artanayasa; I Made Satyawan (Jurnal Inovasi Olahraga, 2026)
This study aims to improve Physical Education, Sports, and Health (PESH) learningoutcomes in the basic techniques of football passing through the implementation of theNumbered Head Together (NHT) cooperative learning model for class XI A2 studentsat SMA Negeri 2 Denpasar during the 2025/2026 academic year. This research wasinitiated by the low learning outcomes of the students, which were reflected in their lackof activeness, cooperation, and mastery of the basic football passing techniques duringthe learning process. This study is a Classroom Action Research (CAR) conducted intwo cycles, with each cycle encompassing planning, action, observation, and reflectionphases. The subjects involved were 39 students from class XI A2 at SMA Negeri 2Denpasar. Data collection was carried out using learning outcome tests for thecognitive aspect, observation sheets for the affective aspect, and skill assessment sheetsfor the psychomotor aspect. The data were analyzed using descriptive statisticalanalysis by calculating the classical learning completeness percentage and comparingthe improvement in learning outcomes across cycles based on the predeterminedsuccess indicators. The results indicated that the implementation of the Numbered HeadTogether (NHT) cooperative learning model effectively enhanced PESH learningoutcomes in the basic techniques of football passing. The classical learningcompleteness percentage reached 82.07%, demonstrating a notable increase comparedto the initial condition prior to the intervention. Improvements in learning outcomesoccurred across the cognitive, affective, and psychomotor aspects, characterized byincreased student activeness, cooperation, responsibility, and mastery of basic footballpassing techniques during the learning process. Consequently, it can be concluded thatthe implementation of the Numbered Head Together (NHT) cooperative learning modelis effective in improving PESH learning outcomes. This learning model can serve as astudent-centered alternative to enhance engagement, interaction, cooperation, andoverall learning outcomes in physical education classes.